The Impact of Coffee and Caffeine on Multiple Sclerosis Compared to Other Neurodegenerative Diseases - Herden, Lena; Weissert, Robert (Frontiers in Nutrition, 2018)
Background: The literature concerning the effect of coffee and caffeine on Multiple Sclerosis (MS) with focus on fatigue is investigated in this review. Potentially clinically relevant effects were also assessed in studies concerning comparable neurodegenerative diseases, such as Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS). Since the existing studies obtained very inconclusive results, we systematically reviewed these studies to summarize the evidence on the possible effects of coffee and caffeine on those disease entities. Previous studies suggested that coffee and caffeine intake is associated with a reduced risk of developing MS and other neurological diseases. Methods: The PubMed database was searched using the keywords “coffee” OR “caffeine” in combination with keywords for each of the different diseases. Besides the keyword search, we included studies by reference list search. Studies on the effects of coffee and caffeine on the single neurological diseases were included for this review. A total of 51 articles met our inclusion criteria. The reviewed articles assessed the impact of coffee on the susceptibility for neurological diseases, as well as the effect of coffee on disease progression and possible symptomatic effects like on performance enhancement. Results: Higher intake of coffee and caffeine was associated with a lower risk of developing PD. In some of the MS studies there is evidence for a similar effect and experimental studies confirmed the positive impact. Interestingly in MS coffee and caffeine may have a stronger impact on disease course compared to effects on disease susceptibility. In ALS no such beneficial effect could be observed in the clinical and experimental studies. Conclusion: This literature assessment revealed that coffee and especially caffeine could have a preventative role in the development of several neurodegenerative diseases, if provided in comparatively high doses. The systematic assessment indicates that coffee and caffeine intake must not be considered as a health risk. Additional clinical studies are needed to fully understand in how far coffee and caffeine intake should be considered as a potential therapeutic approach for certain disease entities and conditions.